Isolation and synthesis of cryptosanguinolentine (isocryptolepine), a naturally-occurring bioactive indoloquinoline alkaloid - Thobokholt Muñoz, Elida Natalia (2020)
Cryptosanguinolentine (isocryptolepine) is one of the minor naturally-occurring monomeric indoloquinoline alkaloids, isolated from the West African climbing shrubCryptolepis sanguinolenta. The natural product displays such a simple and unique skeleton, which chemists became interested in well before it was found in Nature. Because of its structure and biological activity, the natural product has been targeted for synthesis on numerous occasions, employing a wide range of different strategies. Hence, discussed here are aspects related to the isolation of isocryptolepine, as well as the various approaches toward its total synthesis.